Odpowiedzi

2010-01-11T10:09:31+01:00
1.
x3+x2-4x-4=0
x2(x+1)-4(x+1)=0
(x+1)(x2-4)=0
(x+1)(x-2)(x+2)=0
x1=-1, x2=2, x3=-2
2.
x3-x2+4x-4=0
x2(x-1)+4(x-1)=0
(x-1)(x2+4)=0
(x-1)(x-2)(x+2)=0
x1=1, x2=2, x3=-2
3.
x3+x2+9x+9=0
x2(x+1)+9(x+1)=0
(x+1)(x2+9)
(x+1)(x-3)(x+3)=0
x1=-1, x2=3, x3=-3
4.
x3-x2-9x+9=0
x2(x-1)-9(x-1)=0
(x-1)(x2-9)
(x-1)(x-3)(x+3)=0
x1=1, x2=3, x3=-3
5.
x3-4x2-2x+8=0
x2(x-4)-2(x-4)=0
(x-4)(x2-2)=0
(x-4)(x-pierwiastek z 2)(x+pierwiastek z 2)=0
x1=4, x2=pierwiastekz 2, x3=-pierwiastek z 2
6.
x3+3x2-3x-9=0
x2(x+3)-3(x+3)=0
(x+3)(x-pierwiastek z 3)(x+pierwiastek z 3)=0
x1=-3, x2=pierwiastek z 3, x3=-pierwiastek z 3